Overall and Cause-Specific Mortality in Transplant Recipients with a Pretransplantation Cancer History - C Brattström; Fredrik Granath; Gustaf Edgren; Karin E. Smedby; H Wilczek (2013)
It is unclear to what extent cancer history affects posttransplantation mortality in solid organ transplant recipients.We identified a Swedish population-based cohort of solid organ transplant recipients in the National Patient Register 1970 to 2008 and linked it to the Cancer and Cause-of-Death Register. Overall and cause-specific mortality was estimated using Cox regression.Of 10,448 eligible recipients, 416 (4%) had a prior malignancy unrelated to the indication for transplantation diagnosed 2 months or more before surgery (median, 5.7 years). Mortality among cancer history recipients was 30% increased after transplantation, compared with other recipients (adjusted hazard ratio [HR], 1.3; 95% confidence interval [CI], 1.1-1.5; P<0.001), driven by cancer-specific death with no increase in cardiovascular, infectious, or other noncancer mortality. An increased rate of death due to cancer history was primarily observed among nonkidney recipients (adjusted HR(nonkidney), 1.8; 95% CI, 1.3-2.5; HR(kidney), 1.2; 95% CI, 1.0-1.4). Rates were greatest for patients with waiting times of 5 years or less but persisted with waiting times more than 10 years among kidney and nonkidney recipients with prior aggressive cancer types (gastrointestinal, breast, kidney/urothelial, and hematologic malignancies).We conclude that organ transplant recipients with cancer history are at a moderately increased rate of death after transplantation, driven primarily by death due to cancer recurrence.